miR-888 functions as an oncogene and predicts poor prognosis in colorectal cancer - Gao, Su-Jun (Oncol Lett, 2018)
MicroRNAs (miRNAs) are important regulators of tumor formation, progression and metastasis. The present study characterized a novel miRNA (miR)-888, as a potent oncomiR in human colorectal cancer (CRC). The clinicopathological investigation on 126 cases of CRC patients demonstrated that the expression level of miR-888 was significantly upregulated in tumors compared with adjacent healthy tissue, and was associated with tumor stage and histological differentiation. A Kaplan-Meier analysis and log-rank test demonstrated that CRC patients with increased miR-888 expression exhibited a decreased overall survival (OS) and disease-free survival (DFS) compared with patients with low miR-888 expression. Further univariate and multivariate analyses identified miR-888 as an independent prognostic factor for poor survival outcome in CRC patients. To determine the biological role of miR-888 in human CRC, in vitro Cell Counting kit-8, wound healing and transwell assays were performed and demonstrated that miR-888 contributed greatly to CRC cell proliferation, invasion and metastasis. Furthermore, potential targets of miR-888 were investigated using a luciferase reporter assay, followed by polymerase chain reaction and western blot analysis. The findings revealed that miR-888 directly bound to the 3′-untranslated region of mothers against decapentaplegic-4 and thus inhibited its expression and promoted the tumor growth factor-1-induced cancer metastasis signaling. The results of the present study identified miR-888 as an oncogenic miRNA in CRC and provide a foundation for promising research in the future regarding this predictive and prognostic biomarker.